Inclusive Physical Education: Cultivating a Spirit of Involvement in Physical Activity for All Students - Hasmyati (Journal Physical Health Recreation (JPHR), 2025)
Inclusive physical education represents a pedagogical approach that positions every student regardless of physical ability or social background as an active participant in physical activity. This study aims to analyze the concepts, strategies, and key factors influencing the successful implementation of inclusive physical education in schools. A literature-based research method was applied, reviewing national and international studies published between 2019 and 2025. The findings reveal that inclusive physical education positively impacts students’ physical participation, self-confidence, and social empathy. Teachers play a central role in integrating adaptive and differentiated teaching strategies as well as educational technologies such as Augmented Reality (AR) and wearable devices to foster a participatory and equitable learning environment. However, limited facilities, lack of teacher training, and insufficient policy support remain major barriers, particularly in developing contexts such as Indonesia. In conclusion, the success of inclusive physical education depends on the synergy among teacher competence, institutional policy, and cross-sector collaboration to establish adaptive, inclusive, and human-centered physical learning environments for all students.